RETRACTED: On the collision of railcars as an interaction of nonlinear shock wave-like perturbations - D’yachenko A.T.; Abu-Khasan M.S. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001